Missing Jennifer. From image-object to digital product - Valero Cordero, Miriam (Re-visiones, 2024)
After the arrival of the post-internet era we cannot distinguish any more between the life we develop outside and inside the Internet, offline and online. We are learning how to live between the body we inhabit and the images which represents us in the web. In this context, images have started to develop new meanings for the viewer. These meanings are determined by the new circuits in which we insert them: the social networks. In this way, we first see how the image transforms itself into an image-object and then into a digital product.